1987
DOI: 10.1139/y87-262
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the release of atrial natriuretic peptide

Abstract: In assessing the role that atrial natriuretic peptide (ANP) might have in the homeostasis of fluid volume and blood pressure, it is important to define the physiological and pathophysiological conditions that determine its release into the circulation. There is substantial evidence that ANP is released through atrial distension under a variety of conditions. There are also some indications that ANP may be released through humoral factors, although it is not clear whether this is a result of direct action on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, low-dose infusions of ANP over longer periods (hours to days), producing p-ANP concentrations within the Introduction Atrial peptides, a family of cardiac hormones with cardiovascular and renal effects (de Bold et al, 1981;Goetz, 1988), are produced in and released from the heart. Stretch of the atrial wall seems to be the most important releasing factor (for review, see Rankin, 1987), which is reflected by a rise in plasma atrial natriuretic peptide (p-ANP) during mitral obstruction (Ledsome et al, 1985) or volume loading (Lang et al, 1985). The role of ANP as a physiologically important hormone has been questioned, especially as initial studies showed that only supraphysiological concentrations gave any renal response in different experimental models (Goetz, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…However, low-dose infusions of ANP over longer periods (hours to days), producing p-ANP concentrations within the Introduction Atrial peptides, a family of cardiac hormones with cardiovascular and renal effects (de Bold et al, 1981;Goetz, 1988), are produced in and released from the heart. Stretch of the atrial wall seems to be the most important releasing factor (for review, see Rankin, 1987), which is reflected by a rise in plasma atrial natriuretic peptide (p-ANP) during mitral obstruction (Ledsome et al, 1985) or volume loading (Lang et al, 1985). The role of ANP as a physiologically important hormone has been questioned, especially as initial studies showed that only supraphysiological concentrations gave any renal response in different experimental models (Goetz, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that one stimulus for the secretion of atrial natriuretic factor (ANF) is atrial stretch. There is some evidence suggesting circulating hormones may also increase the secretion (Rankin, 1987), and we have shown (Speake et al 1991) a stimulation of secretion with adrenaline and an inhibition with acetylcholine suggesting a possible role for the autonomic nervous system. Adrenaline has also been shown to increase both rate and force of contraction.…”
mentioning
confidence: 50%
“…Taken together, RKIP exerts cardiotoxic effects by multiple pathways (i) as a tumour metastasis suppressor and inhibitor of the RAF1-MAPK axis and (ii) as a GRK2 inhibitor (Figure 7). cAMP signalling and upregulation of natriuretic peptides NPPA and NPPB [162,163]. In support of this statement, Tg-RKIP hearts with symptoms of heart failure showed upregulation of Grk2, which reflects sensitised β-adrenoceptor-stimulated cAMP signalling [142].…”
Section: Summary Of Heart Failure-promoting Functions Of Rkipmentioning
confidence: 77%
“…By sensitisation of the heart failure-promoting Gq/11-coupled AGTR1, RKIP enhances myocardial fibrosis and cardiac hypertrophy [ 10 , 21 , 22 , 23 ]. By sensitisation of cardiac Gs-coupled β-adrenoceptors, RKIP could promote detrimental Gs-stimulated cAMP signalling and upregulation of natriuretic peptides NPPA and NPPB [ 162 , 163 ]. In support of this statement, Tg-RKIP hearts with symptoms of heart failure showed upregulation of Grk2 , which reflects sensitised β-adrenoceptor-stimulated cAMP signalling [ 142 ].…”
Section: Rkip Causes Symptoms Of Heart Failure In Vivomentioning
confidence: 99%